Implementasi Komite Madrasah Sebagai Upaya Peningkatan Mutu Pendidikan Di MAN Gresik - Mulyadi (Jurnal Pendidikan Agama Islam Miazhar, 2021)
The opportunity for madrasas to compete with public schools is very large, as is often stated by observers of Islamic education and officials from the Ministry of Religion, nowadays people are very enthusiastic about sending their children to superior schools that have religious plus values. Madrasas are known as educational institutions that teach religious and general education. According to Husni Rahim, this is a selling point for madrasas. Therefore, if the madrasa is wanted by parents, then improving the quality of education is absolutely necessary. This research use desciptive qualitative approach. This approach is used to obtain data on the implementation of the madrasah committee at MAN Gresik and the efforts it has made. The research design uses an embedded case study model. In accordance with the research problem, the informants or subjects in this study were administrators and members of the madrasa committee at Madrasah Aliyah Negeri Gresik. To obtain the desired data, using in-depth interview techniques, observation, documentation The implementation of the madrasa committee at MAN Gresik is still not optimal. The data analysis technique used is descriptive-explorative. This is caused by several factors, among others; The madrasa establishment system is still top-down. This is contrary to the basic concept of a bottom-up madrasa committee. The recruitment system for madrasah committee members is heavily influenced by the proximity factor to the madrasah principal, so that it affects the independence and existence of madrasa committees that are easily manipulated. The role of the madrasa committee is not optimal and the APBM is not participatory so that the madrasa committee is not considered as a working partner for madrasas. The madrasa committee does not yet have a concrete work program to empower madrasah because the madrasa committee management does not yet have original ideas and only follows a five-year program that has been designed by the madrasah. Based on the results of these studies the researchers recommend; To optimize the madrasa committee, ethics and manners are needed, especially monitoring budget transparency to avoid tug-of-war and psychological burdens and the socialization of the madrasa committee needs to be improved so that there is no misperception.